Effect of Sanitation on Health of Prisoner Physical in Class IIA Bekasi - Muhammad Fahrurroji (Bisma The Journal of Counseling, 2020)
Health for prisoners is very important and good sanitation is a factor in creating health itself. The purpose of this study was to determine the condition of the sanitation factors that influence the health conditions of inmates in Bekasi Class IIA Penitentiary. This type of research is quantitative descriptive with the cross-sectional approach by comparing independent variables and dependent variables identified only once and at the same time. From the results of the dissemination and evaluation by the prisoners. The results showed that the condition of residential cells in Lapas Class IIA Bekasi was good. This can be seen from the average obtained on the condition of residential cell forging conditions that show a scale above 4, which means the respondents agree that the condition of the residential cell is good. Based on research conducted by researchers in Bekasi Class IIA Lapas, it shows that the sanitation condition of Lapas affects the health conditions of prisoners. Following the concept of the epidemiological triangle of causes and processes of disease occurrence.